The Role of Adult Education in the Process of Rethinking the Past and its Impact on Democratization. A Case Study in Eastern Europe - Tetyana Kloubert (Adult Education Research Conference, 2014)
This paper will present the results of a research project that deals with the topic coming to terms with the past as a problem of adult education. This project aims to define and describe dealing with a totalitarian past in educational institutions and its impact on civic education. It concentrates on Poland, Russia and Ukraine.